Analisis Faktor Pemilihan Makanan pada Dosen dan Karyawan Universitas Ahmad Dahlan pada Era Adaptasi Baru - Cita Eri Ayuningtyas; Yunda Maymanah Rahmadewi; Irbah Umaniyah; Evita Dwi Yulianti (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2021)
Background; Food choice is the most important factors that caused disease. The prevalence of non communicable diseases in Indonesia is quite high due to unhealthy lifestyle changes. Food choice in new adaptation era influenced by emotional eating. Work rhythms changed by workshift schedule can lead stress triggers unhealthy lifestyle for example food consumption. Objectives; to analyze food choice for UAD’s staff in new adaptation era. Material and Method; type of research used qualitatif study fenomenology design. This research was conducted in Universitas Ahmad Dahlan among the staff (Lecturers and employees). Totally 4 respondents recruited in this reseach. Information collected by indepth interview through online meeting platform and being recorded during the interview. Results; the study found there was no difference the type of food consumed between before and during new adaptation era. The choice of food used delivery order system to avoid virus transmission by the crowds. Respondents have a habit coffee and tea consumption everyday for distraction a stress . Conclusion; it was found that there was no difference the type of food between before and during the new adaptation era Covid-19. Factors to be considered of food choice were virus transmission, food safety, avoid the crowds and alternatively used the delivery order system. There was favorite drinks consumed everyday.